2019
DOI: 10.1103/physrevb.99.195405
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation and node states in bilayer graphene systems

Abstract: We investigate the electronic structure of realistic partial dislocation networks in bilayer graphene that feature annihilating, wandering, and intersecting partial lines. We find charge accumulation states at partials that are sensitive to Fermi energy and partial Burgers vector but not to the screw versus edge character of the partial. These states are shown to be current carrying, with the current density executing a spiral motion along the dislocation line with a strong interlayer component to the current.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…for a twist bilayer the AB or AA stacked bilayer), and |φ X corresponding plane wave states. This approach has been fully described in 27 , and used to treat optical deformations in graphene in 28 , and partial dislocations in bilayer graphene in 19,20,30 . In what follows we describe in overview the methodology, in particular how it pertains to lattice relaxation in the twist bilayer, but refer the reader to these references for further details.…”
Section: B Model Relaxation Fieldmentioning
confidence: 99%
“…for a twist bilayer the AB or AA stacked bilayer), and |φ X corresponding plane wave states. This approach has been fully described in 27 , and used to treat optical deformations in graphene in 28 , and partial dislocations in bilayer graphene in 19,20,30 . In what follows we describe in overview the methodology, in particular how it pertains to lattice relaxation in the twist bilayer, but refer the reader to these references for further details.…”
Section: B Model Relaxation Fieldmentioning
confidence: 99%
“…For further details we refer the reader to Ref. 20 as well as several applications of the method: to minimally twisted bilayer graphene 18 , partial dislocation networks [21][22][23] , and in-plane deformation fields 24,25 .…”
Section: Effective Hamiltonian Theorymentioning
confidence: 99%
“…It is found that the presence of LSWs can lead to rich conductance features even in the single particle transport regime. It is argued that transport energy gaps in the meV regime are not caused by an electronic instability due to electronic interactions as typically assumed [39; 40], but simply due to the structure of transport across LSWs and, in particular, due to "hot" charge carrying LSWs [41]. A similar argument for the presence of plateaus at fractional fillings [42][43][44] in BLG is made in [45], where arbitrary fractional plateaus are engineered in artificial SLG mosaics interconnected with metallic strips.…”
Section: Introductionmentioning
confidence: 99%